Investigating a caregiver-assisted social skills group programme for primary and early high school-aged children with acquired brain injury or cerebral palsy: protocol for a pilot mixed-methods, two-group randomised trial of PEERS Plus - Koa Whittingham; Roslyn N Boyd; Rose Gilmore; Leanne Sakzewski; Nicola Hilton; Afroz Keramat; Bianca Thompson; Jacqui Barfoot; Christine T Moody (BMJ Open)
Introduction Reaching social milestones is an important goal of childhood. Children with acquired brain injury (ABI) and cerebral palsy (CP) frequently experience challenges with social functioning and participation. The Programme for the Education and Enrichment of Relational Skills (PEERS) is a group-based social skills programme for adolescents. This study will compare an adapted PEERS programme with usual care in a pilot randomised waitlist-controlled trial for primary and early high school-aged children with brain injuries.Methods and analysis This single-centre study will be conducted at the Queensland Cerebral Palsy and Rehabilitation Research Centre at the Centre for Children’s Health Research in Brisbane, Australia. Thirty-two school-aged children (grades 3+; 8–13 years) with an ABI or CP and their caregiver(s) will be recruited and randomly assigned to either 12 week PEERS Plus or waitlist usual care. The waitlist group will then participate in PEERS Plus after the 3 month retention time point. The primary outcome will measure individualised social participation goals on the Canadian Occupational Performance Measure immediately postintervention at the primary endpoint (12 weeks). Secondary outcomes include the Social Skills Improvement System Social-Emotional Learning Edition Rating Forms and Quality of Play Questionnaire immediately postintervention, 12 weeks postintervention (26 weeks postbaseline), 36 weeks postintervention (52 weeks postbaseline) for retention. Following completion of the PEERS Plus programme, semistructured focus group interviews will be conducted separately with caregivers and children to explore the lived experience of PEERS. Interpretive description will be used to identify patterns and themes related to participants’ experiences. Analyses will follow standard principles for randomised controlled trials using two-group comparisons on all participants on an intention-to-treat basis. Comparisons between groups for primary and secondary outcomes will be conducted using regression models. This study will estimate the unit costs of providing PEERS Plus at different levels of public health facilities in Australia.Ethics and dissemination This study has been approved by the Medical Research Ethics Committee of The University of Queensland (2022/HE002031) and the Children’s Health Queensland Hospital and Health Service Human Research Ethics Committee (HREC/22/QCHQ/87450). Recruitment and participant informed consent process will be completed in accordance with institutional ethic procedures. Dissemination plans include peer-review publication of study results, presentations, and instructional workshops at national and international conferences.Trial registration number ACTRN12623000515695.